ChemInform Abstract: Synthesis of Some New 3‐Coumaranone and Coumarin Derivatives as Dual Inhibitors of Acetyl‐ and Butyrylcholinesterase. Issue 51 (17th December 2013) - Alipour, Masoumeh; Khoobi, Mehdi; Nadri, Hamid; Sakhteman, Amirhossein; Moradi, Alireza; Ghandi, Mehdi; Foroumadi, Alireza; Shafiee, Abbas
Abstract The title compounds (III), (VI) exhibit inhibitory activity against both AChE and BuChE in the micromolar range.